Land-use and road development pattern of downtown makassar since 19th century until now - A. Akil (Lowland Technology International, 2017)
The study aims to determine the development of land use and road patterns in downtown Makassar since 19th century and its influencing factors. The study intends to provide an understanding of the growth and development direction of the city based on the history, to figure out the factors which later can be used as a basis of coastal city planning policy. The collection of information obtained by observation, in-depth interviews, and referring to the city development history. The data were analyzed using GIS-based spatial technique and qualitative analysis to determine factors that affect urban development. The study found that land uses such as residential, trade/services, port, and social facilities have been developing dynamically in the downtown Makassar until nowadays. These phenomenon lead to subsiding or disappearance of other land uses such as paddy fields, township, gardens, open spaces, grave, and jail. The development ware strongly influenced by the dynamics of economic development, science, and urban technology, especially on trade and settlement facilities. The direction of urban development is dominant to the East and South due to the availability of vacant land and access to hinterland. Similarly, the development of roads in the downtown area also occurs dynamically as the loss of some roads as a result of infrastructure and housing construction. It is strongly associated with urban urbanization process due to the modernization. Facing that, it is necessary to maintain urban heritage strategy among others: actualization of local wisdom and heritage, involving each ethnic in development, revitalizing area based on history and culture, and area management.